PEMAHAMAN PENDIDIK TENTANG HAKEKAT KEMANUSIAAN DAN APLIKASINYA DALAM LINGKUNGAN PSIKOLOGIS DALAM PROSES PEMBELAJARAN - Ida Umami (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2015)
This research generally aims to get brief description of teachers’ understanding aboutnstudents and its implication in learning process. Specifically, the purpose of this research are to get description about: 1) teachers understanding about students and its defferences among variables, 2) the implementation of high touch unsure in learning process according to teachers’ and students and defferences among them, 3) the contribution of teachers, understanding about student toward high touch applied in learning process and, the different response between teachers and students about high touch implementation. This research is conducted by descriptive quantitative method. The population is all teachers and students at senior high school in Padang. Samples are taken by using stratified cluster random sampling technique. The percentage, correlation and t test. The results of this research reveal that: 1) everall, teachers understanding is in middle category, so is with the implementation toward learning process, 2) five observable variables about the nature of man are valid and can be used to explain teachers’ understanding about the nature of man as laten variable, and six observable variables about high touch implementation as implication of teachers’ understanding about student in learning process. Therefore, teachers understanding about student has positive and significant correlation with implementation of teachers’ understanding about nature of man toward learning process trough high touch implementation, and 3) teachers’ opinion about high touch implementation as implication of teachers’ understanding toward learning process differ significantly with students’ opinion. In general, teachers’ opinion score is higher compared with student’s opinion score.Kata kunci: Pemahaman dan Persepsi Pendidik, Hakekat Kemanusiaan, Lingkungan Psikologis dalam Pembelajaran